Assessing the international criminal court with the organizational effectiveness approaches - Abdel Megeed, Heba Yehia (AUC Knowledge Fountain, 2016)
The International Criminal Court (‘the ICC’), located in the Hague, Netherlands, the first permanent court tasked with prosecuting the most severe crimes happening internationally. It is critical to assess the effectiveness of the ICC while in reality, there is no consensus on the criteria that should be employed to that end. There are no standards that its stakeholders and observers can refer or agree to in order to assess the Court’s effectiveness. The purpose of this research is to develop a new approach to this issue. It proposes to use the approaches of Organizational Effectiveness Theory in order to gain a much firmer grasp of the issue. The research analyses the ICC through the prism of international governmental organizations, merely one monograph has attempted to use this theory in assessing the effectiveness of international courts. This research utilizes the four main approaches of Organizational Effectiveness Theory, namely the Goal Approach, the System Recourse Approach, the Strategic Consistency Approach and the Contradiction Approach. However, this is not an empirical study of the ICC, but rather an evaluation the relevance of each approach in assessing the effectiveness of the ICC. According to the current analysis, not all of the main organizational effectiveness theory approaches are sufficiently relevant. It concludes that the contradictions approach is the most relevant since it offers the possibility to overcome the main limitations of the other approaches. The research contends that observers can best assess the ICC by evaluating its ability to maintain the required balance among its contradicting interests that guarantees its survival. The conclusion that the contradictions approach should be employed in assessing the ICC as soon as there is an agreement in relation to the Court’s basic performance indicator